Composition‐Dependent Long‐Term Stability of Mosaic Solid‐Electrolyte Interface for Long‐Life Lithium‐Ion Battery. Issue 11 (4th August 2021) - Rao Rikka, Vallabha; Ranjan Sahu, Sumit; Chatterjee, Abhijit; Gopalan, R.; Sundararajan, G.; Prakash, Raju
Abstract: The solid‐electrolyte interface (SEI) layer determines the fast charging capability and cycle life of a lithium‐ion battery. In‐depth investigation of the mosaic SEI layer's formation, growth, and stability are of utmost importance to obtain a stable electrochemical performance over cycles. We investigate the stability of the mosaic SEI layer during cycling at a high C‐rate (0.5 C). The composition of the SEI layer is governed by the current density‐dependent formation of inorganic and organic compounds. The inorganic compounds rich outer SEI layer and organic compounds rich inner SEI layer formed after the first lithiation helps in preventing SEI breakdown and growth during cycling. The SEI layer densifies during cycling as a result of the decomposition of the entrapped electrolyte. The composition‐dependent stability of the mosaic SEI layer stability opens up new possibilities for extending the cycle life of lithium‐ion batteries. Abstract : Long live the battery : Cycle life of Li‐ion batteries is dependent on the stability of the solid‐electrolyte interface (SEI) layer. This study presents a comprehensive analysis on the formation, growth, stability of the SEI layer in terms of current density‐dependent sequential formation of SEI compounds. The SEI densifies during cycling due to the decomposition of the entrapped electrolyte.